M72 - knife gate valves - MacConnell, Mark (American Water Works Association, 2020)
"This manual presents the general practice for selection and installation of manual and automated knife gate valves for use in water and waste-water applications. This document is intended to provide information and guidance on typical knife gate valves and their intended application"-- Provided by publisher
Keywords: Water-pipes -- Valves -- Handbooks, manuals, etc.; elektronické knihy; electronic books